Rancangan Sistem Informasi Finansial berbasis Emas dengan Penerapan Blockchain - Muhammad Agung Rizkyana (Ikatan Ahli Informatika Indonesia, 2020)
Inflation in currencies involving several countries in the world. About 3% to more than 25% of the value of currencies has decreased in 2019. Inflation is a decrease in the value of money occurring at a wide price and lasts for a certain period. This event occurred on currency (paper and metal). One reason is that the money material has no intrinsic value, is easy to install and disseminate, and money no longer produces gold as a standard exchange rate. Gold has an intrinsic value that is resistant to value. Information technology through application media that runs on information systems. The information system that manages savings, payments, transfers, investments and other financial-related activities. Meanwhile, the present situation shows that gold is no longer a substitute for commodities that can be traded. Information systems are supported to produce gold as the basis for money spent in the system. To manage transactions, this information system applies blockchain technology as the backbone of transactions. Existing data on a transaction in the Blockchain cannot be changed, each data changes according to encryption in the next block. Also, the blockchain is distributed to every user in the blockchain and transactions will be backed up. Users must use a computer connected to the internet network. The purpose of this study is to discover the potential of the blockchain system so that it can be used in gold-based financial information systems. The information system makes gold as a base for resistant transactions and gives confidence to the user.